1985
DOI: 10.1093/clinchem/31.12.1997
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholinesterasemia with isoenzymic alteration in a family.

Abstract: A family with hypercholinesterasemia with isoenzymic alteration is reported. The propositus, a 55-year-old woman, was admitted to our hospital because of diabetes mellitus. Because her cholinesterase activity (delta pH 3.2) was supranormal, with no other abnormal liver-function test result throughout the hospitalization period, and was independent of her disease state, we investigated whether this condition might be familial. We studied six of her 17 family members in three generations. All six had above-norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[9][10][11][12] Furthermore, in some families, genetic hypercholinesterasaemia has been reported, but elevation of plasma cholinesterase activity is not known to affect the hemodynamics of the central and peripheral nervous system. [13][14][15][16] Neitlich 13 reported that one person with high serum cholinesterase activity was more resistant to succinylcholine and a muscle relaxant than were normal subjects. In contrast, the diseases associated with low cholinesterase activity are reported in liver disease, myocardial infarction, and collagen diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Furthermore, in some families, genetic hypercholinesterasaemia has been reported, but elevation of plasma cholinesterase activity is not known to affect the hemodynamics of the central and peripheral nervous system. [13][14][15][16] Neitlich 13 reported that one person with high serum cholinesterase activity was more resistant to succinylcholine and a muscle relaxant than were normal subjects. In contrast, the diseases associated with low cholinesterase activity are reported in liver disease, myocardial infarction, and collagen diseases.…”
Section: Discussionmentioning
confidence: 99%